The reduced-tillering trait (tin) is not beneficial under wheat cropping systems that allow for moderate to high water-limited yields - Francesca Mureddu; Rosella Motzo; Franz-Werner Badeck; Fulvia Rizza; Francesco Giunta (Frontiers in Agronomy)
Reduced-tillering wheat (Triticum aestivum L.) lines carrying the tin (tiller inhibition) gene are characterized by high spike fertility and high grain weights. These traits may enable high yields under favorable climatic conditions, provided that the low tillering is offset by an adequate sowing rate. Field trials were conducted to evaluate the effect of the tin gene by comparing two pairs of near-isogenic lines (NILs), namely Janz ± tin and Kite ± tin, sown at a rate of 350 germinable seeds m-² across six environments (two sites × three years) in Italy (Sardinia and Emilia-Romagna). Seasonal rainfall (October–May) ranged from 311 to 784 mm, corresponding to mean grain yields between 3.5 and 6.7 t ha-1. On average, the tin lines yielded similarly to their free-tillering counterparts (4.67 vs. 4.78 t ha-1, respectively), owing to their higher grain weight (45.0 vs. 42.3 mg), which compensated for a lower grain number (10408 vs. 11554 m-²) resulting from fewer spikes m-2 (406 vs. 437), despite a similar number of grains per spike. The reduced fruiting efficiency of tin lines (56.0 vs. 65.6 grains g-1 of spike), likely due to an inefficient investment in chaff, may have constrained the expression of their typically high spike fertility. However, the lower spike number plasticity in tin lines was balanced by greater plasticity in grain weight, enabling comparable grain yield plasticity between NILs. Although the grain yield level and plasticity of tin lines were comparable to those of free-tillering lines, these results do not support their adoption in cropping systems targeting moderate to high yields. On the other hand, the findings do not rule out the potential benefits of introgressing tin genes into different genetic backgrounds or improving fruiting efficiency to overcome the limitations identified in this study.